2011
DOI: 10.1074/jbc.m111.261677
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin and β-Catenin Act in a Regulatory Loop in Dermal Fibroblasts to Modulate Cutaneous Healing

Abstract: ␤-Catenin is an important regulator of dermal fibroblasts during cutaneous wound repair. However, the factors that modulate ␤-catenin activity in this process are not completely understood. We investigated the role of the extracellular matrix in regulating ␤-catenin and found an increase in ␤-catenin-mediated Tcf-dependent transcriptional activity in fibroblasts exposed to various extracellular matrix components. This occurs through an integrin-mediated GSK3␤-dependent pathway. The physiologic role of this mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 74 publications
0
62
0
2
Order By: Relevance
“…This has been demonstrated in mice treated with an adenovirus expressing the Wnt signaling inhibitor Dickkopf (DKK1, which binds LRP6/Arrow), without a significant decline in ß-catenin protein levels during the proliferative phase of skin wound healing, in contrast to the situation in bone repair. 39 This suggests that other factors play a role in regulating ß-catenin levels during the proliferative phase of healing. Indeed, ß-catenin levels in fibroblasts can be stimulated by growth factors, such as TGF-ß1, which are released during the early stages of wound repair.…”
Section: Proliferationmentioning
confidence: 99%
“…This has been demonstrated in mice treated with an adenovirus expressing the Wnt signaling inhibitor Dickkopf (DKK1, which binds LRP6/Arrow), without a significant decline in ß-catenin protein levels during the proliferative phase of skin wound healing, in contrast to the situation in bone repair. 39 This suggests that other factors play a role in regulating ß-catenin levels during the proliferative phase of healing. Indeed, ß-catenin levels in fibroblasts can be stimulated by growth factors, such as TGF-ß1, which are released during the early stages of wound repair.…”
Section: Proliferationmentioning
confidence: 99%
“…Fibronectin has also previously been shown to play a role in fibroblast activation (53,54), so we tested whether addition of fibronectin alone to RSM could rescue FAK Fibroblast Activation in the TME clustering and fibroblast activation, but we did not see a rescue of FAK clustering (Fig. 5 C), or fibroblast activation (Fig.…”
Section: Both CCL Growth Factors and Serum Fibronectin Are Necessary mentioning
confidence: 68%
“…5). Others have suggested that the matrix FN-EDA can lead to fibroblast activation, but plasma fibronectin has also been shown to alter fibroblast activity in a wound healing model (53,63). Perhaps some fibronectin domains such as FNIII10, which is conserved between plasma and matrix FN and interacts with integrin avb3 (62), are necessary for proper integrin engagement and clustering to allow for activation, whereas other domains such as EDA actually stimulate activation.…”
Section: Discussionmentioning
confidence: 97%
“…Color images available online at www.liebertpub.com/tea A significant role for macrophages has been shown during skin healing and hypertrophic scar formation. [41][42][43][44] While their presence is essential, increased numbers of macrophages lead to hypertrophic scarring, a morbidity that should be avoided. As such, it is important to evaluate whether the hydrogel augments inflammation to avoid unnecessary scarring.…”
mentioning
confidence: 99%